SPIRITUAL EDUCATION : SOLUSI TERHADAP DEKADENSI KARAKTER DAN KRISIS SPIRITUALITAS DI ERA GLOBAL - Susanti, Salamah Eka (Humanistika : Jurnal Keislaman, 2016)
Among the negative consequences of this global era, is the spiritual values of religion is not only practiced, but a scourge in life. Religious values separate from life. Religion is only for the afterlife, and world affairs not related to religion. With the advancement of science and technology, making some people move away from religion. Even had freed mankind from God completely. Globalization piggybacking liberalism, hedonism and secularism. Hedonic live culture has become peoples behavior. Hedonist lifestyle issues is what caused the Moral decadence, promiscuity (free sex), especially among young teens who carry HIV / AIDS, the destruction of the family institution and the proliferation of illicit drug abuse (narcotics). Developments in this modern age makes us get up in the fields of industry and modern technologies. But since due to advances in the field of material that then we run into problems of spiritual paralysis. Basically, every human being has the ethical values that are essential in him, which is the spiritual soul. Therefore, the real men are spiritual beings. But sometimes the spiritual dimension is overlooked to the spirituality that exists within him naturally (nature) is less able to provide the function of anything against him. The loss or neglect of the spiritual dimension of mans cause less significant (meaning) of his life at the same time less able to control the entire action. Thus the spiritual dimension must be maintained and more developed. To be able to do this, hence the need for spiritual education for man that his soul alive and not barren. Spiritual education can deliver humans to be individual character. Sufficient spiritual strength that will make people able to make changes. Worship consciously or unconsciously will develop an attitude of life, nature will, behavior and finer and reduce the despicable character. Without the light of faith (spiritual) one will not be able to recognize themselves, to know the depth of his true identity, the purpose of the universe, or even know what is going on behind all that appears in front of him.Â